Pancreatic Cancer Methods and Protocols - Su, Gloria H.; Su, Gloria H. (Methods in Molecular Medicine,, 2005)
In the last decade, major progress has been made in identifying the critical oncogenes and tumor-suppressor genes that can cause pancreatic cancer. In Pancreatic Cancer: Methods and Protocols, leading clinicians and scientists from prestigious research institutes and cancer centers present in readily reproducible format the classical techniques that have contributed to these advances in pancreatic research and introduce new strategies that should produce future breakthroughs across the field of cancer biology. The authors provide a broad range of methods for the molecular, biochemical, pathological, and statistical analyses of both sporadic and familial pancreatic cancers, methods that can be applied not only to basic, but also to translational pancreatic research. Topics covered include in vitro cell cultures, in vivo mouse models, protein studies, mutation analysis, and treatment development. The protocols follow the successful Methods in Molecular Medicine™ series format, each one offering step-by-step laboratory instructions, an introduction outlining the principle behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Comprehensive and highly practical, Pancreatic Cancer: Methods and Protocols offers those interested in either basic or translational research an ambitious collection of essential yet novel methods for pancreatic cancer research, methods that can also readily be applied broadly throughout cancer research.